Optimization, encapsulation and characterization of bromelain-generated angiotensin I-converting enzyme (Ace) - inhibitory hydrolysates from stone fish (Actinopyga lecanora Jaeger) - Auwal, Shehu Muhammad (2018)
Stone fish is an under-utilized sea cucumber with many nutritional and ethno-medicinal values. Proteases-aided hydrolysis of stone fish protein was found to generate hydrolysates with strong antioxidant and ACE-inhibitory effects. However, the direct use of stone fish-derived hydrolysates as potential antihypertensive molecules is limited by their low stability against digestive enzymes and unpleasant fishy odor. Therefore, the present study aimed to optimize hydrolysis of stone fish protein for the production of angiotensin I-converting enzyme (ACE)-inhibitory hydrolysates using bromelain and improve the stability and ACE-inhibitory activity of the resulting hydrolysates against gastrointestinal digestion by nanoencapsulation. Response surface methodology (RSM) based on a central composite design (CCD) was used to model and optimize the degree of hydrolysis (DH) and ACE-inhibitory activity. A pH of 7.0, temperature of 40oC, E/S ratio of 2% and reaction time of 240 min were determined using a response surface model as the optimum levels to obtain the hydrolysates with maximum ACE-inhibitory activity of 84.26% at 44.59% degree of hydrolysis. The hydrolysates were further profiled in which five novel ACE-inhibitory peptides including ALGPQFY, KVPPKA, LAPPTM, EVLIQ and EHPVL were identified with their respective IC50 values of 0.012 mM, 0.980 mM, 1.31 mM, 1.44 mM and 1.68 mM. The ACE-inhibitory hydrolysates were then nanoencapsulated in chitosan nanoparticles and optimized based on 3-factor 3-level Box–Behnken experimental design. The optimized nanoparticles showed a good physicochemical stability following their twelve weeks of storage at 4oC. The result of in vitro efficacy indicated significantly higher (p˂0.05) ACE-inhibitory activity of 51.96% for the nanoparticles compared to 36.84% for the free hydrolysates following their simulated gastrointestinal digestion. The in vivo antihypertensive effect of the optimized nanoparticles was also evaluated on spontaneously hypertensive rats within 24 h following single oral administration at 200 mg/kg, 400 mg/kg and 800 mg/kg. The results demonstrated significant systolic blood pressure lowering effects of the nanoparticles at all the three doses compared to the group treated with the unencapsulated hydrolysates. The nanoparticles were then evaluated for acute and sub-acute toxicity on liver and kidney of Wistar Kyoto rats. The result indicated no death with a safe dose limit of the nanoparticles greater than 2000 mg/kg. Serum biochemical analysis and histomorphological examination following 28 days of repeated exposure of the rats to the 200 mg/kg, 400 mg/kg and 800 mg/kg doses of the nanoparticles, revealed no alteration in the function and architecture of both liver and kidney with no occurrence of cellular necrosis. This indicated the safe therapeutic application of the chitosan nanoparticles loaded with stone fish-derived ACE-inhibitory hydrolysates to be utilized as food bio-ingredient for long term management of hypertension.